Performance analysis of both sex marathon runners ranked by IAAF - Perez, A. J.; Marques, A.; Bolonha Gomes, K. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2018)
Running a marathon has become the motivation to achieve success and economic independence for athletes, mainly from African countries. This feeling is more evident among the black community, considering that they have been presenting better results than white athletes. The objective of the study was to analyse the ranking of marathon runners around the world, in the last 15 years considering: 1) nationality; 2) best average time of the 100 best classified runners from the Top 100, Top 50, Top 25, Top 10 and Top 3. An analysis was made to the ranking available on the International Association of Athletics Federations (IAAF) website, for the 100 best world results for both sexes, focusing on records from 2000 to 2014. The analysis was subdivided into ranking groups (Top 3, 10, 25, 50 and 100), resulting in 3000 records. African runners, Kenyan and Ethiopian, dominate the male ranking representing 70% of the total of runners in Top 100, keeping this proportion up to Top 3. African runners, Kenyan and Ethiopian, dominate the male ranking representing 70% of the total of runners in Top 100, keeping this proportion up to Top 3. The same is observed for females, however with a significantly lower percentage (34%), with Japanese, Ethiopian and Kenyan (17%) and an English athlete as the world record. The average time of a marathon has been decreasing in males more than in female competitions, both in Top 3 and Top 10, however still presenting a large gap from world records.